STRUKTUR POPULASI TERNAK BABI DI DESA SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Patty, Sonaya; Joseph, Godlief; Rehatta, Lea Marylin (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to determine the population structure of pigs in Suli Village, Salahutu District, Central Maluku Regency. The research was conducted over one month using a total sampling method involving all 44 pig farmers and all pigs they owned. The collected data included the number of pigs based on age groups (piglet, weaner, grower, finisher, and breeder) and sex. The results showed that the total pig population in Suli Village was 754 heads, consisting of 227 males and 246 females in the non-breeding group, as well as 77 adult males and 204 sows in the breeding group. The age structure was dominated by breeders (37.27%) and piglets (30.37%), while the finisher group had the lowest proportion (1.99%). The overall male-to-female ratio was 1:1.5, indicating a favorable population condition for sustainable reproduction. In conclusion, the pig population structure in Suli Village demonstrates a relatively stable production potential, characterized by a high number of breeders and continuous regeneration, providing a solid basis for the development of pig farming in the area.